2015
DOI: 10.1016/j.tics.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Do humans make good decisions?

Abstract: Human performance on perceptual classification tasks approaches that of an ideal observer, but economic decisions are often inconsistent and intransitive, with preferences reversing according to the local context. We discuss the view that suboptimal choices may result from the efficient coding of decision-relevant information, a strategy that allows expected inputs to be processed with higher gain than unexpected inputs. Efficient coding leads to ‘robust’ decisions that depart from optimality but maximise the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
134
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 57 publications
14
134
0
1
Order By: Relevance
“…In our analyses, however, we assumed that such direct and unbounded gain amplification is not plausible because organisms operate within computational and metabolic constraints (33). Due to these constraints, even under conditions of increased vigilance behavioral and neural variability perseveres (34), indicating that a portion of internal noise is virtually irreducible.…”
Section: Discussionmentioning
confidence: 99%
“…In our analyses, however, we assumed that such direct and unbounded gain amplification is not plausible because organisms operate within computational and metabolic constraints (33). Due to these constraints, even under conditions of increased vigilance behavioral and neural variability perseveres (34), indicating that a portion of internal noise is virtually irreducible.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the stochastic normalized utility function defined in Equation 16 because of its neuroscientific underpinnings and its ability to explain context-sensitive preferences in valuebased decision-making (Summerfield & Tsetsos, 2015). Concretely, UWS combined with a context-insensitive utility function, such as a simple linear function of the outcome, or the concave utility function of prospect theory, would be unable to explain why people's preference for the risky gamble +40/0 over the safe option +20 is lower in Experiment 3 than in Experiment 1 even though the choices are exactly the same.…”
Section: Overweighting Of Extreme Events In Decisions From Experiencementioning
confidence: 99%
“…We chose it because it is the simplest instantiation of the efficient coding theory proposed by Summerfield and Tsetsos (2015) that captures our findings. It thus remains to be validated independently.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, perceptual decisions are prone to deviate from the veridical as seen in phenomena such as sensory illusions (7,25). Recent theoretical work has suggested that these "biases" reflect humans' ability to deal with the uncertainties in the world using the probabilistic structure of the environment (26,27). Therefore, seemingly erroneous judgments are not only very common in the course of evolution (28) but are also optimal and rational (29)(30)(31).…”
Section: Fig 2 (A)mentioning
confidence: 99%